2011
DOI: 10.1111/j.1468-3083.2011.04168.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin disorders and the role of dermatologists after the tsunami in Japan

Abstract: JEADV percentage was 9.6% on days 11-20 and increased to about 21% on days 41-49 (Fig. 1). We think that the skin-disorder patients refrained from consulting a doctor right after the disaster because they felt that patients with life-threatening diseases should have priority. Skin disease, however, significantly reduces the evacuees' quality of life and more patients have started consulting doctors for skin problems.Dermatologists have an important role after a huge natural disaster like a tsunami, as there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…Chronology of the major health impacts. Days from the disaster Main healthcare issue Within 24 hours Few injuries4 2-10days Hypothermia4 , 5 Endogenous diseases4 Burning4 ‘Tsunami-lung’5 Psychiatric shock4 Cardio-pulmonary arrest (CPA)6 Coronary syndrome6 Cerebro-vascular diseases7 ‘drug-refugees’25 10-30days Respiratory diseases8 , 9 , 11 Gastritis8 , 9 Pressure ulcers39 Exacerbation of chronic conditions24 Allergic reactions to tsunami debris8 >30days Children with allergy13 Musculoskeletal disease2 , 17 , 38 Deep venous thrombosis (DVT) and pulmonary embolism15 , 16 Throughout Non-communicable diseases24 (hypertension, diabetes, chronic renal failure, cancer, etc. )Pregnancy hypertension4 , 8 Oxygen-dependent management11 , 42 Insomnia6 Skin-related disorders18 Suspected Mental health (depression, posttraumatic stress disorder (PTSD) , and cognitive disorder among the elderly)41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronology of the major health impacts. Days from the disaster Main healthcare issue Within 24 hours Few injuries4 2-10days Hypothermia4 , 5 Endogenous diseases4 Burning4 ‘Tsunami-lung’5 Psychiatric shock4 Cardio-pulmonary arrest (CPA)6 Coronary syndrome6 Cerebro-vascular diseases7 ‘drug-refugees’25 10-30days Respiratory diseases8 , 9 , 11 Gastritis8 , 9 Pressure ulcers39 Exacerbation of chronic conditions24 Allergic reactions to tsunami debris8 >30days Children with allergy13 Musculoskeletal disease2 , 17 , 38 Deep venous thrombosis (DVT) and pulmonary embolism15 , 16 Throughout Non-communicable diseases24 (hypertension, diabetes, chronic renal failure, cancer, etc. )Pregnancy hypertension4 , 8 Oxygen-dependent management11 , 42 Insomnia6 Skin-related disorders18 Suspected Mental health (depression, posttraumatic stress disorder (PTSD) , and cognitive disorder among the elderly)41 …”
Section: Resultsmentioning
confidence: 99%
“…For example, 15% of the patients who visited temporary clinics had skin problems 19. Others noted an increase in muscle pain, constipation,18 insomnia, headache,7 and vision problems 20. As these patients often refrained from seeing doctors due to the lack of transportation infrastructure, the numbers might be underestimated 20…”
Section: Resultsmentioning
confidence: 99%
“…They can occur while people return to clean damaged homes, suffering skin injuries from treading on nails, getting fingers cut, or falling. 27 A previous study found the risk of injury was 2.9-times higher for people over 65 years old. 12 A diminished capacity to recover from harm or adopt preventative measures may be one factor.…”
Section: Discussionmentioning
confidence: 94%
“…One study suggests skin infections or traumatic skin disorder are linked to cleaning damaged homes. 27 Another study revealed that elderly patients with limited mobility had a higher incidence of skin diseases such as pressure ulcers because of a scarcity of resources, manpower, and access to utilities. 32 Skin diseases peaked twice on Day 5 and Day 11.…”
Section: Discussionmentioning
confidence: 99%
“…Among adults, wounds and minor trauma emerged as the prevailing health events and occurred predominantly during the acute phase rather than immediately following the disaster. This may reflect that adults were often injured while cleaning and repairing their homes in the wake of the disaster [34].…”
Section: Discussionmentioning
confidence: 99%